Comprehensive Guidance and Counselling Program: The Beechville-Lakeside-Timberlea Experience - Graham-Migel, Janice (Canadian Journal of Counselling and Psychotherapy, 2007)
This manuscript provides an overview of the Comprehensive Guidance and Counselling Program in the Beechville-Lakeside-Timberlea (B-L-T) Community. It focuses on program development, including the needs assessment and description of programs designed to meet specific needs of students (self-esteem, anger management, conflict resolution, study skills, work habits, career education, peer support programs, student wellness, the B-L-T Teen Health Centre, etc.), program evaluation, staff training, and community involvement. This overview illustrates how the Comprehensive Guidance and Counselling Program takes on the challenge of meeting the needs of the whole person in children and adolescents.